Enhanced virulence of Beauveria bassiana against Diatraea saccharalis using a soluble recombinant enzyme with endo- and exochitinase activity (2020)
Beauveria bassiana chitinases are involved in degrading the chitin in insects’ exoskeletons and internal structures, and thus are important virulence factors as they participate in initial to final steps of infection. In this work, the B. bassiana (Bv062 isolate) open reading frame (ORF) encoding a chitinase identified as Chit37 (orthologous Bvchit1) was molecularly cloned and expressed in Escherichia coli, and the potential of the recombinant protein (rChit37) to enhance the insecticidal activity of Bv062 conidia against second instar Diatraea saccharalis larvae was studied. rChit37 was produced in both soluble and insoluble fractions of an E. coli culture. Both fractions expressing endo- (90 mU/µL) and exochitinase (170 mU/µL) enzymatic activity, with optimum conditions for enzyme activity of 45 °C and pH 5.0. His-tag affinity chromatography was used to purify the rChit37 from the soluble fraction. Purified rChit37 was then diluted to 200 and 300 µg/mL for use as Bv062 conidia additive (1x106con/mL) in a laboratory bioassay against D. saccharalis larvae. No significant differences were observed between the efficacy of Bv062 conidia applied alone or mixed with 200 µg/mL purified rChit37. However, 300 µg/mL rChit37 increased BV062 conidia insecticidal activity, achieving 96.7% efficacy (14 days post-infection) and 6.2 days median lethal time (LT50), compared to 60% efficacy and 8.9 days for conidia alone. rChit37 addition did not affect conidial viability in terms of germination (96.6% after 24 h) or vigour estimated as germ-tube elongation rate. This work provides proof of concept about soluble recombinant chitinase as an additive to enhance B. bassiana virulence against D. saccharalis. © 2020 The Authors